Multi Sensor Integrated System for Wireless Monitoring of Green-House Environment - Ripal Raj, Saurabh, Prashant Anand, Prashant Kumar , Neethu K N (International Journal of Advanced Science and Technology, 2020)
In this modern era which is advancing in technologies day by day, a good agricultural infrastructure is very important. For good agricultural yield, an ideal environment is very much needed which can only be done inside the greenhouse. In greenhouse environment many parameters are used to monitor and control the environment such as light sensor, humidity sensor, CO2 sensor, temperature sensor. To monitor all these parameters wirelessly ZigBee technology is used here. The system consists of transmitter station which consist of all the sensors, receiver station and a monitoring system.